Crochet in a Day 42 Fast and Fun Projects - Truman, Emily ([London] Stackpole Books, 2019)
Looking for a quick crochet fix? Crochet in a Day has 42 sure-to-please patterns that can all be started and finished in a day or less. From wearables like cowls, hats, slippers, and even a poncho, to home items like place mats, dish cloths, and baskets, every item will crochet up fast!
1
Keywords: CRAFTS & HOBBIES / Needlework / Crocheting